Studies on the Electrochemical Behavior of Sulfite on Incoloy 800 in a Neutral Environment - Mihaela-Alexandra Lăboșel; Andrea Kellenberger; Mircea Laurențiu Dan; Nataliia Rudenko; George-Daniel Dima; Nicolae Vaszilcsin (Applied Sciences)
Avoiding atmospheric pollution with sulfur dioxide is generally achieved by its absorption from combustion gases in alkaline solutions and conversion to sulfites. Afterwards, sulfites can be transformed into neutral and environmentally safe chemicals by oxidation to sulfates. The oxidation of sulfites to sulfates can also be carried out in a cell in which the fuel will be sulfite ions. In this way, in addition to the beneficial effect of neutralizing large quantities of sulfite waste, electrical energy is also obtained. This is one of the reasons why study of the anodic oxidation of sulfite to sulfate on various electrode materials was necessary. Given the sensitivity of electrode materials in the presence of sulfur compounds, in our research we approached the study of sulfite oxidation on the Incoloy 800 anode in neutral solution (1 mol L−1 Na2SO4). In this research, the results obtained in the study of the kinetic parameters of the anodic process as a function of the sulfite concentration (10−1, 0.5, and 1 mol L−1), using linear voltammetry, are presented. The appreciable values of the exchange current density (3.4, 3.0, and 2.6 A m−2) show that Incoloy 800 has a significant catalytic effect in the anodic oxidation of sulfite. Chronoamperometric studies have shown that the anodic oxidation of sulfite is controlled by the mass transfer of sulfite ions from the bulk solution to the electrode surface. According to the chronocoulometric diagrams, it can be appreciated that, up to anodic potentials of +1.50 V, sulfite oxidation occurs on the electrode, while at more positive potentials, the oxygen evolution reaction is the main process. Electrochemical impedance data provide evidence of a chemical reaction coupled with electron transfer, which was modeled using a Gerischer impedance. At high sulfite concentrations, the charge transfer resistance (Rct) decreases by a factor of 10, indicating that the sulfite oxidation reaction is fast at sufficiently positive potentials. On the other hand, the passivation tendency of stainless steels upon anodic polarization gives them a high corrosion resistance, so that Incoloy 800 can be a viable option as an anode material for sulfite/oxygen (air) fuel cells.